Study on Hysteresis Curve Characteristic of Input Shaft of Harmonic Reducer - Tang Xiaohuan; Wang Xiangjiang; Feng Dongyan (Jixie chuandong)
A test device of torsional stiffness and hysteresis of the harmonic drive reducer are described and its experimental study is carried out. The output shaft of the harmonic gear is fixed,one- way gradual change torque is applied to the input shaft and a protractor instrument is applied to measure the rotation angle of the input shaft. To deal with measurement data,the hysteresis curve equation of input shaft is fitted by using the data. Through many times measurement experiments,the test result show that the hysteresis curve equation and several actual measurement error below 3. 8%. According to the results of different load torque value,the hysteresis of harmonic gear primarily is caused by deformation of flexspline lag,all parts of the manufacturing,installation errors and the clearance between the transmission chain.